How Does the Combination of Muslim Consumption Index and Halal Product Campaign Affect Consumer Preferences in the Bandung Halal Culinary Sector? - Mahmudah, Siti; Rahmani Hakim, Latifa Dinar; Andiani, Paramita (West Science Social and Humanities Studies, 2025)
This study examines the impact of the Muslim Consumption Index (MCI) and halal product campaigns on consumer preferences in Bandung's halal culinary sector. Using a quantitative approach, data were collected from 250 respondents and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that both MCI and halal product campaigns significantly influence consumer preferences, with halal product campaigns showing the strongest direct effect. Furthermore, the interaction between MCI and halal product campaigns demonstrates a synergistic effect, amplifying consumer trust and preference for halal-certified culinary products. These results highlight the importance of aligning intrinsic Islamic values with strategic marketing efforts to drive consumer engagement in the halal market. Practical implications for businesses include leveraging ethical branding and strengthening halal campaigns to build trust and loyalty. Policymakers are encouraged to support halal certification programs and foster innovation in marketing strategies to enhance the sector’s growth.